2017
DOI: 10.1002/ccd.26884
|View full text |Cite
|
Sign up to set email alerts
|

Deep sedation Vs. general anesthesia in 232 patients undergoing percutaneous mitral valve repair using the MitraClip® system

Abstract: The MitraClip implantation performed using DS is as safe and effective as MitraClip implantation performed using GA. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
4
18
0
1
Order By: Relevance
“…Our study confirms the results of previous studies that demonstrated the safety and efficacy of MitraClip ® procedures using DS [ 2 ; 3 ; 10 ]. Only one patient (1.5%) had to be converted to GA due to respiratory depression, which is a low conversion rate and consistent with previous reports [ 2 ; 5 ]. Procedural success was achieved in 100% of the patients irrespective the difficulty of DS.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our study confirms the results of previous studies that demonstrated the safety and efficacy of MitraClip ® procedures using DS [ 2 ; 3 ; 10 ]. Only one patient (1.5%) had to be converted to GA due to respiratory depression, which is a low conversion rate and consistent with previous reports [ 2 ; 5 ]. Procedural success was achieved in 100% of the patients irrespective the difficulty of DS.…”
Section: Discussionsupporting
confidence: 91%
“…No in-hospital deaths occurred. We previously reported in a larger study that mortality did not differ between MitraClip ® procedures using DS and procedures using GA [ 2 ]. These mortality rates are comparable to those reported for MitraClip ® procedures using GA, which have been reported as 2.5% in the TRAMI registry [ 11 ] and 4.8% in the EVEREST II high-risk study [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations